The Reflections of Feminist Ideas in Novels and Short Stories by Slovenian Women Writers - Mihurko Poniž, Katja (Poznańskie Studia Slawistyczne, 2016)
Slovenian authors who contribute to the feminist and later lesbian discourse are often also the poets and writers. As far as the feminist and lesbian theory tradition is concerned, the connection to western theories is present. Slovenian women writers and their female characters think about the options of a female subject position, they reflect their own dilemmas and issues in the creative process. While the character of a heterosexual feminist is still marginal in modern Slovenian literature, the character of a lesbian realizing the demands of radical feminism has become a self-evident part of the Slovenian literary production with the works of Suzana Tratnik and Nataša Sukič.